Adapting Indonesian Accounting Programs to Digitalization and Sustainability: Challenges and Responses - Pradana, Bartolomeus Galih Visnhu; Ambarriani, Anastasia Susty; Sunarni, Ch. Wiwik (Universitas Pendidikan Ganesha, 2025)
This study explores how accounting academic programs in Indonesia respond to the evolving roles of the accounting profession amid digitalization and the sustainability era. There is a widespread perception that digital technologies may reduce the demand for accountants by replacing human roles with automation. A mixed-method approach was employed, combining qualitative and quantitative data collection through surveys, documentation review, observations, in-depth interviews, and a Focus Group Discussion (FGD) with accounting professionals and educators. The findings reveal those technological advancements—such as financial reporting software and IT applications—have significantly transformed accounting tasks by simplifying and accelerating financial statement preparation. However, the participants emphasize that foundational accounting knowledge remains indispensable. IT tools cannot replace accountants, as their role extends beyond report preparation to include financial data analysis and interpretation. Accounting education in Indonesia is adapting by integrating information technology skills alongside traditional accounting principles to ensure professionals remain relevant in a digital and sustainability-driven environment. The study calls for accounting curricula to include digital skills, ethics, and sustainability to better prepare graduates.